Medicinal Compound Extraction from the Whole Body of Cynodon Dactylon (L.) Pers. by Using Hot Water - Ramali, Azlan (Universiti Teknologi PETRONAS, 2016)
Cynodon Dactylon (L.) Pers is a type of perennial grass that can be commonly found almost anywhere in the world, especially in tropical area. Recent studies show that a number of chemical constituents can be extracted from the plant, as well as the medicinal compounds. The objectives of this project were to extract medicinal compunds from the whole part of Cynodon Dactylon using three different methods and to analyze the constituents through GC-MS analysis. The samples was collected from one location in Perak. In this study, three extraction solvents was used which were ethanol, methanol and hot water. Ethanolic extraction and methanolic extraction were done through soxhlet extraction while for hot water extraction batch reactor was utilized in batch extraction. Extracted samples were analyzed using GC-MS and the chromatograph was analyzed to get the chemical constituents presented in the samples.